Thoughts on the usage of audible smiling in speech synthesis applications - Trouvain, Jürgen; Weiss, Benjamin (Frontiers in Computer Science, 2022)
In this perspective paper we explore the question how audible smiling can be integrated in speech synthesis applications. In human-human communication, smiling can serve various functions, such as signalling politeness or as a marker of trustworthiness and other aspects that raise and maintain the social likeability of a speaker. However, in human-machine communication, audible smiling is nearly unexplored, but could be an advantage in different applications such as dialog systems and individual speech prostheses. The rather limited knowledge of the details of audible smiling and their exploitation for speech synthesis is a great challenge. This is also true for modeling smiling in dialogs and testing it with users. Thus, the paper aims to identify findings and challenges of how to use the acoustic channel of smiling in synthetic speech.